2018
DOI: 10.1093/icvts/ivx445
|View full text |Cite
|
Sign up to set email alerts
|

In search of the best xenogeneic material for a paediatric conduit: an experimental study†

Abstract: Each xenogeneic material requires individual anticalcification strategy. DE + CEABA pretreatment demonstrates a high mineralization-blocking efficacy for the bovine pericardium and should be employed to further develop the paediatric pericardial conduit. Aortic wall calcification cannot be blocked completely using this strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 23 publications
3
15
1
4
Order By: Relevance
“…Both PAW and BJVW are elastin‐rich biomaterials; however, they differ in the dominant components of the extracellular matrix (elastin in PAW and collagen in BJVW) (Zhuravleva et al, 2018). Elastin is extremely prone to calcification in both untreated biotissues and those cross‐linked with aldehydes or epoxides (Bailey et al, 2003; Perrotta et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Both PAW and BJVW are elastin‐rich biomaterials; however, they differ in the dominant components of the extracellular matrix (elastin in PAW and collagen in BJVW) (Zhuravleva et al, 2018). Elastin is extremely prone to calcification in both untreated biotissues and those cross‐linked with aldehydes or epoxides (Bailey et al, 2003; Perrotta et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Высокая скорость кальцификации данного типа кондуита обусловлена структурными особенностями аортальной стенки [21,22]. Большое количество эластиновых волокон и остаточных гладкомышечных клеток способствует высокой скорости отложения кальция в ткани [23][24][25]. Учитывая особенности метаболических процессов у детей, способствующие более ранней кальцификации ксеногенной ткани [1,3,9], мы считаем, что использование кондуитов, содержащих ксеногенный аортальный корень, нежелательно в педиатрической группе больных.…”
Section: врожденные пороки сердца Congenital Heart Diseaseunclassified
“…Данное обстоятельство указывает на то, что использование ДЕ-обработанных ксеноперикардиальных кондуитов может быть потенциально перспективным для протезирования ЛА у детей. Однако остается необходимым дальнейшее развитие дополнительных методов антикальциевой обработки этого типа кондуитов [25].…”
Section: врожденные пороки сердца Congenital Heart Diseaseunclassified
See 1 more Smart Citation
“…[1][2][3][4][5] However, some experimental studies showed benefits of biomaterial cross-linking with epoxy compounds as well. Epoxy compounds provide better resistance to calcification in comparison with GA. [6][7][8] Other advantages of epoxy compounds include less immunogenicity and cytotoxicity, as well as less negative effects on the mechanical properties of tissues. 9,10 Our institute has extensive experience in using different types of xenografts, including diepoxy-treated bovine pericardial valved conduits (DE-PVC) for RVOT reconstruction in children and adults.…”
Section: Introductionmentioning
confidence: 99%